IPAS Learning Assessment To Measure Science Process Skill In Elementary School - Hardiansyah, Framz; Misbahudholam AR, Muhammad; Hidayatillah, Yetti (Universitas Pendidikan Ganesha, 2022)
The results of the needs analysis show that the learning process in schools has been carried out but has not been utilized optimally. This study aims to develop an assessment to measure science process skills and to determine the feasibility of developing an assessment. The type of research used is Research and Development (R&D). The development model used is 4-D with 4 stages: define, design, develop, and disseminate. The subjects of this study were 30 grade 4 students. The data analysis technique used in this study is the percentage of product eligibility criteria, reliability, using reliability test criteria, differentiating power analysis, using differentiating criteria. The results of developing an assessment to measure science process skills in science subjects in elementary schools were obtained from the validation of 73.3% assessment experts, 89.28% material experts, and 89.28% linguists. The feasibility of the science assessment to measure students' science process skills is based on expert validators; the results meet the requirements and are based on the validity of valid and reliable test items that can be used to measure science process skills. The items are stated to be good and reliable so that they can be used to measure science process skills. Making science learning assessments to measure science process skills requires a team of experts, so the questions developed need more references to produce quality, creative and varied questions.